Sarcopenia as a comorbidity-independent predictor of survival following radical cystectomy for bladder cancer - Mayr, Roman; Gierth, Michael; Zeman, Florian; Reiffen, Marieke; Seeger, Philipp; Wezel, Felix; Pycha, Armin; Comploj, Evi; Bonatti, Matteo; Ritter, Manuel; van Rhijn, Bas W. G.; Burger, Maximilian; et al. (Journal of cachexia, sarcopenia and muscle, 2018)
BACKGROUND: A multicentre study was conducted to investigate the impact of sarcopenia as an independent predictor of oncological outcome after radical cystectomy for bladder cancer. - METHODS: In total, 500 patients with available digital computed tomography scans of the abdomen obtained within 90 days before surgery were identified. The lumbar skeletal muscle index was measured using pre-operative computed tomography. Cancer-specific survival (CSS) and overall survival (OS) were estimated using Kaplan-Meier curves. Predictors of CSS and OS were analysed by univariable and multivariable Cox regression models. - RESULTS: Based on skeletal muscle index, 189 patients (37.8%) were classified as sarcopenic. Patients with sarcopenia were older compared with their counterparts (P = 0.002), but both groups were comparable regarding to gender, comorbidity, tumor, node, metastasis (TNM) stage, and type of urinary diversion (all P > 0.05). In total, 234 (46.8%) patients died, and of these, 145 (29.0%) died because of urothelial carcinoma of the bladder. Sarcopenic patients had significantly worse 5 year OS (38.3% vs. 50.5%; P = 0.002) and 5 year CSS (49.5% vs. 62.3%; P = 0.016) rates compared with patients without sarcopenia. Moreover, sarcopenia was associated independently with both increased all-cause mortality (hazard ratio, 1.43; 95% confidence interval 1.09-1.87; P = 0.01) and increased cancer-specific mortality (hazard ratio, 1.42; 95% confidence interval, 1.00-2.02; P = 0.048). Our results are limited by the lack of prospective frailty assessment. - CONCLUSIONS: Sarcopenia has been shown to be an independent predictor for OS and CSS in a large multicentre study with patients undergoing radical cystectomy for bladder cancer.
Gesehen am 24.03.2020